Assessment of motor imagery ability and training - André Luiz Felix Rodacki; Joice Mara Facco Stefanello; Claudio Portilho Marques (Revista Brasileira de Cineantropometria e Desempenho Humano, 2010)
The aim of this study was to evaluate changes in motor imagery ability in response to a specific dart throwing training. Twelve subjects (17-22 years) with no previous experience in dart throwing or imagery agreed to participate. Changes in imagery ability were assessed using the Sports Imagery Questionnaire before (pretreatment) and after (post-treatment) an imagery training program consisting of 10 sessions. Retention (RET) was assessed 2 weeks after training. The program included mental exercises designed to develop vivid images, to control one’s own images, and to increase perception about performance. Comparison of the imagery training conditions (training alone, training accompanied, observing a colleague, and during assessment) showed no differences between the pretreatment, post-treatment and RET evaluations. Although imagery ability did not respond to training, significant differences between imagery domains (visual, auditory, kinesthetic, and animic) were found (p<0.05), except between the visual and animic domains (p=0.58). These differences might be related to subject’s domain preference subject during the imagery process and to the nature of the task in which the skill technique used seems to be a relevant aspect.